2018
DOI: 10.1142/s0219498818501591
|View full text |Cite
|
Sign up to set email alerts
|

Embeddings of right-angled Artin groups into higher-dimensional Thompson groups

Abstract: In this paper, we construct embeddings of right-angled Artin groups into higher dimensional Thompson groups. In particular, we embed every right-angled Artin groups into n-dimensional Thompson groups, where n is the number of complementary edges in the defining graph. It follows that Z n * Z embeds into nV for every n ≥ 1. IntoductionThe Thompson group V is an infinite simple finitely presented group, which is described as a subgroup of the homeomorphism group of the Cantor set C. Brin [1] defined higher dimen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…the set of all pairs of generators that do not commute. Kato has subsequently strengthened this result to n = |E c | [11]. Kato's bound is not sharp, and it remains an open problem to determine the smallest n for which a given right-angled Artin group embeds into nV .…”
Section: Introductionmentioning
confidence: 99%
“…the set of all pairs of generators that do not commute. Kato has subsequently strengthened this result to n = |E c | [11]. Kato's bound is not sharp, and it remains an open problem to determine the smallest n for which a given right-angled Artin group embeds into nV .…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, Theorem 3.29 applies, so that V κ splits as a semidirect product Γ D b (Q, x) where Γ is a graph product of free groups, so a right-angled Artin group, and [Bri04]. But nV does not embed into V , for instance because nV contains the free product Z 2 * Z (initially proved in [Cor13], and reproved in [BBM16] for n ≥ 5 and in [Kat18] for n ≥ 2), which is not a subgroup of V according to [BSD13, Theorem 1.5].…”
Section: Applicationsmentioning
confidence: 99%
“…Proposition 5.4 implies that, if nV embeds into a braided diagram group, then it must embed into Thompson's group V since nV is simple according to [Bri04]. But nV does not embed into V , for instance because nV contains the free product Z 2 * Z (initially proved in [Cor13], and reproved in [BBM16] for n ≥ 5 and in [Kat18] for n ≥ 2), which is not a subgroup of V according to [BSD13, Theorem 1.5]. Now, we will deduce from Theorem 5.1 some criteria to show that a diagram group embeds into some Thompson's group and we will apply them to the examples we mentioned in Section 2.4.…”
Section: Main Embeddingmentioning
confidence: 99%
“…In light of this, it was conjectured in [2] that Z d * Z is the correct obstruction for embeddability in the Brin-Thompson group (d − 1)V defined in [3]. In [2], it was shown that at least RAAGs with m nodes and n non-commuting relations embed in (m + n)V. In [6], it was proved that if G is a RAAG with Z d * Z ≤ G, then indeed G ≤ (d − 1)V, as predicted by the conjecture. In this paper, we refute the conjecture from [2] and completely settle the issue of RAAG embeddability: all (countable) RAAGs embed in nV for all n ≥ 2.…”
Section: Introductionmentioning
confidence: 99%